1965
DOI: 10.1002/pssb.19650120215
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐Magnetophonon Resonance in Semiconductors

Abstract: A theory is presented for spin‐magnetophonon resonance. The spin interaction of electrons with optical phonons is described by the introduction of vector and scalar potentials of the optical vibrational field. It is shown that the spin‐magnetophonon resonance should cause a minimum in the longitudinal magnetoresistance. The experimental data for n‐InSb and n‐InAs are discussed on the basis of this theory. Certain new magnetoresistance measurements are presented for the case of n‐InSb: 1) A maximum of the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

1968
1968
1975
1975

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Now when we have taken into account the effect of the conduction band nonparabolicity on the scattering probability, the effect of electron-phonon interaction on m, and eg, and the screening of the deformation and polarization potentials, the agreement was attained throughout the range of used pressures. The good agreement between calculation and experiment, obtained in [3] for the thermoelectric power at high pressures, is due to the fact the thermoelectric power depends more weakly on scattering than the mobility (the expression for the thermoelectric power does not contain t), and therefore the mentioned three factors, essentially affecting the value of the mobility, cause a very small change in the thermoelectric power. low temperatures.…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…Now when we have taken into account the effect of the conduction band nonparabolicity on the scattering probability, the effect of electron-phonon interaction on m, and eg, and the screening of the deformation and polarization potentials, the agreement was attained throughout the range of used pressures. The good agreement between calculation and experiment, obtained in [3] for the thermoelectric power at high pressures, is due to the fact the thermoelectric power depends more weakly on scattering than the mobility (the expression for the thermoelectric power does not contain t), and therefore the mentioned three factors, essentially affecting the value of the mobility, cause a very small change in the thermoelectric power. low temperatures.…”
mentioning
confidence: 68%
“…In addition it is worth noting that our measurements of the dependence p ( P ) up to 15 kbar at 78 O K on samples with n = 8.3 x l O l 6 and 4.8 x 1018 cm-3 showed that the agreement between values of p experimental and calculated under assumption /ell = 40 eV is not affected by the change of the degree of nonparabolicity. Thus, one can conclude that the temperature corrections due to nonparabolicity do not introduce large errors into the value of el, for at pressures from 20 to 25 kbar the degree of nonparabolicity decreases appreciably : at 25 kbar 5 / E g is more than three times smaller than at atmospheric pressure.e) But whereas at high temperatures there are no obvious reasons, which could lead to appreciable errors, one can point out a weak spot in the calculations at eV/deg and -2.9 x a) It was noted in our paper [3] that the discrepancy between calculated and experimental values of the mobility for a sample with n = 2.4 x 10'8 om-3 at T = 290 O K is larger at smaller pressures. Now when we have taken into account the effect of the conduction band nonparabolicity on the scattering probability, the effect of electron-phonon interaction on m, and eg, and the screening of the deformation and polarization potentials, the agreement was attained throughout the range of used pressures.…”
mentioning
confidence: 83%
See 3 more Smart Citations